Detectando diferencias en la medición de la calidad del resultado: Evidencia empírica para empresas espa\~nolas - Cristina Ferrer García; José Antonio Laínez Gadea (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2013)
– Earnings quality is not a measurable concept through only one variable, but there are several attributes that characterize earnings quality and employing one or another could influence the research conclusion without considering one of them the best measure of earnings quality. The study deals with measuring earnings quality through different alternatives used in previous literature. Then, we study there are significant differences among these different methods to measure the same attribute using the Friedman test. The results of this study demonstrate that not only the earnings attribute is crucial to assess earnings quality, but also the different ways of measuring them could determine the results. Thus, through the results, we can say that is a key issue for any research on earnings quality, defining and measuring this concept properly, since the results and conclusions may be determined by that decision.
Keywords: M41; 330; accounting quality; earnings attributes; discretionary accruals; accruals quality; earnings smoothing; Friedman test